A lithium supplement and preparation method thereof, and lithium ion battery
By coating the conductive polymer on the surface of the lithium supplement precursor, the problem of lithium-rich oxide oxidation in the air is solved, the lithium ion conductivity and electron conductivity are improved, the battery life is extended and the energy density is improved.
Patent Information
- Application Number
- CN202411433921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Lithium-rich oxides are easily oxidized in the air and react with moisture in the air, leading to gelation during the coating of the positive electrode material, affecting the expected effect of lithium supplement agents.
By coating the conductive polymer on the surface of the lithium supplement precursor, especially adding water reducers, dispersants and surfactants to the conductive polymer, a gel-like cladding layer is formed to improve the lithium ion conductivity and electron conductivity.
It improves the performance of lithium-rich materials' croquette capacity at lower charging voltages, reduces their sensitivity to moisture and carbon dioxide in the air, extends the service life of the battery and increases the energy density.
Smart Images

Figure CN118970053B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium supplement and a preparation method thereof, and a lithium ion battery. Background Art
[0002] When lithium-ion batteries are charged for the first time, there will be processes such as SEI film formation, anode material particle shedding and irreversible deposition of lithium metal, which consumes active lithium ions from the cathode material and reduces the battery's available energy. However, the energy density of conventional lithium-ion battery cathode materials is already close to the theoretical value, and how to further improve the energy density has become a research hotspot.
[0003] Lithium-rich oxide (Li x MO y ) As a high-capacity positive electrode lithium supplement material, it has received more and more attention in the industry. However, lithium-rich oxides are easily oxidized in the air and react with moisture in the air to form lithium hydroxide. When the lithium hydroxide content is too high, the slurry will gel during the coating process of the positive electrode material, making the coating impossible, which greatly affects the expected effect of the lithium supplement. Therefore, it is necessary to modify the lithium-rich material to improve the lithium ion conductivity and electronic conductivity of the lithium-rich material, thereby improving the gram-to-gram capacity of the lithium-rich material at a lower charging voltage, while reducing its sensitivity to moisture and carbon dioxide in the air and reducing its harsh use conditions. Summary of the invention
[0004] The present invention aims to solve the above problems by providing a lithium supplement and a preparation method thereof, and a lithium ion battery, so as to solve the problems of poor air stability and poor conductivity of lithium-rich materials during storage.
[0005] To achieve the above-mentioned object, the present invention provides a lithium supplement agent, which includes a lithium supplement agent precursor and a conductive polymer, wherein the conductive polymer is coated on at least a portion of the surface of the lithium supplement agent precursor; wherein the lithium supplement agent precursor includes Li5FeO4; an additive is added to the conductive polymer, and the additive includes at least one of a water reducer, a dispersant and a surfactant.
[0006] The lithium supplement precursor is used to supplement lithium in lithium-ion batteries, and at least part of the surface of the lithium supplement precursor is coated with a conductive polymer. Conductive polymer coating can improve the capacity of the lithium supplement during the electrochemical cycle, thereby increasing the battery energy density and extending the battery life. Conductive polymers can enhance the overall conductivity of the lithium supplement, allowing lithium ions to migrate more quickly and efficiently within the battery, improving the battery's charge and discharge performance. The coating layer can optimize the interface compatibility between the lithium supplement and the battery electrolyte, reduce potential interface reactions, reduce internal resistance, and further improve battery efficiency.
[0007] The introduction of conductive polymers, especially with the assistance of at least one of additives such as water reducers, dispersants and surfactants, can protect the inner core by forming a gel-like coating layer while compensating for the microcracks on the surface of the inner core of the lithium supplement, so that the anti-fluorite structure of the inner core of the lithium supplement will not be converted into a disordered lithology or amorphous form before its capacity is exerted. In addition, conductive polymers can increase conductivity to solve the problems of poor air stability and poor conductivity of lithium-rich materials during storage.
[0008] In any of the above technical solutions, the conductive polymer includes at least one of poly(p-phenylene vinylene), polyaniline, polyphenylene sulfide, polypyrrole, polyacetylene, and polythiophene; and / or the water reducer includes melamine resin; and / or the dispersant includes at least one of polyvinyl pyrrolidone and coconut acid monoethanolamide; and / or the surfactant includes at least one of hexadecyltrimethylammonium bromide, monolauryl phosphate, alcohol ether phosphate, coconut acid diethanolamide, and cocamidopropyl dimethylamine ethyl lactone.
[0009] Different types of conductive polymers have their own conductivity, stability and chemical properties. Among them, materials such as polyaniline and polypyrrole have excellent conductivity and good mechanical stability, while polyphenylene sulfide and polythiophene provide good heat resistance and chemical stability. By selecting different conductive polymers, the conductivity, mechanical strength and compatibility of the lithium supplement with the battery electrode can be adjusted.
[0010] As a water reducer, melamine resin can effectively reduce the viscosity of the conductive polymer solution, making it easier to evenly coat the surface of the lithium supplement precursor during the preparation process. At the same time, it can also improve the processability of the lithium supplement during the manufacturing process and prevent excessive adhesion and delamination of the material during the coating process.
[0011] Polyvinyl pyrrolidone and coconut acid monoethanolamide are used as dispersants to effectively prevent the conductive polymer from agglomerating during the preparation process and ensure that the material maintains good dispersion in the solution, which helps to obtain a more uniform coating layer during the coating process while ensuring that the conductive polymer forms a stable network structure on the surface of the precursor.
[0012] Surfactants can significantly improve the interfacial tension between the conductive polymer and the lithium supplement precursor during the coating process, thereby enhancing its adhesion. These surfactants can improve the wettability of the conductive polymer, allowing it to more evenly cover the lithium supplement precursor and form a dense conductive layer. In addition, surfactants can also reduce interfacial defects that may occur during the coating process, such as pinholes and cracks.
[0013] In any of the above technical solutions, the thickness of the coating layer formed by the conductive polymer on the surface of the lithium supplement agent precursor is 5nm-20nm; and / or the particle size D50 of the lithium supplement agent is in the range of 7μm-20μm; and / or the particle size Dmax of the lithium supplement agent is in the range of Dmax≤50μm; and / or the added amount of the conductive polymer is 1wt%-3wt% of the lithium supplement agent.
[0014] By controlling the thickness of the conductive polymer coating within the range of 5nm-20nm, a balance between effective conductivity and economical material use can be achieved. Too thin a thickness will result in insufficient conductivity and the inability to form a continuous conductive path; while too thick a thickness will result in material waste and may increase the internal resistance of the battery, thereby affecting battery performance. In addition, reasonable thickness control can also enhance the adhesion and stability of the conductive layer, reduce delamination or splitting caused by mechanical or electrochemical stress during the cycle, and improve the overall durability and cycle life of the battery.
[0015] The median diameter D50 of the particle size reflects the central trend of the particle size distribution of the lithium supplement. Controlling the particle size D50 of the lithium supplement within the range of 7μm-20μm helps to ensure the uniform distribution of the lithium supplement particles in the battery and optimize its contact area with the electrolyte. Smaller particle sizes are conducive to improving reaction activity and uniformity, while overly large particles will lead to poor contact between particles and affect battery performance. Therefore, the particle size distribution within this range helps to optimize the surface-to-volume ratio of the lithium supplement and improve its electrochemical performance during the battery reaction. At the same time, reasonable particle size control can prevent the sedimentation or accumulation of particles in the battery, ensuring the uniform discharge characteristics and long life of the battery.
[0016] The maximum particle size of the lithium supplement is controlled within 50μm, which can prevent the stratification or agglomeration caused by larger particles during the coating process, thereby affecting the distribution and conductivity of the lithium supplement inside the battery. The control of particle size ensures the uniformity of the material during the coating process and avoids the damage of the conductive network by the presence of large particles. At the same time, this control also helps to optimize the electrode structure and interface quality inside the battery, further improving the performance stability and service life of the battery.
[0017] The amount of conductive polymer added is controlled to be between 1wt% and 3wt% of the total weight of the lithium supplement, while maintaining good conductivity, and avoiding the use of excessive conductive polymer to prevent excessive impact on the properties of the lithium supplement material itself, such as mechanical strength or reactivity. An amount of conductive polymer added below 1wt% may not form a sufficient conductive path, while an amount exceeding 3wt% may increase costs and negatively affect the physical properties of the material.
[0018] The present invention provides a preparation method of a lithium supplement agent, comprising the following steps: S10, pulverizing and sintering a lithium source and an iron source in sequence to obtain a lithium supplement agent precursor; S20, dissolving the lithium supplement agent precursor in an organic solvent to obtain a mixture; S30, adding the mixture to a conductive polymer, stirring and drying in sequence to obtain the lithium supplement agent; wherein an additive is added to the conductive polymer, the additive comprises at least one of a water reducer, a dispersant and a surfactant, and the amount of the additive added is 0.2wt%-2wt% of the conductive polymer.
[0019] The invention discloses a preparation method for preparing a lithium supplement agent, wherein the crushing and sintering steps accurately control the particle size and crystal structure of a lithium supplement agent precursor, which is conducive to the efficiency and uniformity of subsequent chemical reactions; the lithium supplement agent precursor is dissolved in an organic solvent to ensure the uniform distribution of chemical components, which is the key to optimizing subsequent reactions and product performance. Specifically, the lithium supplement agent precursor is Li5FeO4 generated by sintering, which is dissolved in an organic solvent to enable LFO to be better combined with a conductive polymer to finally form an LFO core in the product; the introduction of the conductive polymer, especially with the assistance of additives such as a water reducer, a dispersant and a surfactant, not only improves the conductivity of the lithium supplement agent, but also improves its mechanical strength and stability, so that the lithium supplement agent is more suitable for use in batteries, and has better electrochemical properties and a longer service life.
[0020] In this preparation method, the conductive polymer can be evenly coated on the surface of the lithium supplement core. A water reducer, dispersant or surfactant is added to the conductive polymer to avoid the problem of large particle agglomeration during the coating process, enhance the fluidity of the material, and obtain a denser gel-like film, which can eventually be more evenly attached to the lithium supplement core. The gel-like conductive polymer not only covers the LFO surface, but also fills the microcracks in the LFO core, increases the strength of the LFO, and prevents the lithium supplement core from being converted into a disordered rock phase or amorphous form before the capacity is exerted, ensuring better capacity.
[0021] In the process of preparing conductive polymers, the amount of additives added is precisely controlled between 0.2wt% and 2wt% of the total weight of the polymer. This ratio range is designed to ensure that the additives can work effectively while avoiding unnecessary cost increases or possible negative effects caused by excessive use. By controlling the amount of additives, while enhancing the performance of the polymer, controlling costs and avoiding the additional burden caused by excessive addition; mechanical strength or other related properties, without interfering with the basic structure of the material.
[0022] In any of the above technical solutions, the lithium source includes at least one of LiOH, Li2CO3, Li2O, Li2O2, LiNO3, Li2SO4, C6H5Li3O7, Li2C2O4, C2H5OLi, and metallic lithium; and / or the iron source includes at least one of Fe2O3, Fe3O4, Fe(OH)3, and FeO(OH); and / or the organic solvent is at least one of tetrahydrofuran, N-methylpyrrolidone, and dimethyl sulfoxide; and / or the molar ratio of the lithium source to the iron source is (5-7): 1; and / or after the lithium source and the iron source are crushed, their particle size D50 is 5μm-70μm.
[0023] Lithium sources have different chemical properties and reactivity, which provide multiple possibilities for the preparation process, thereby adjusting the performance and efficiency of the lithium supplement. The choice of iron source affects the magnetic and structural stability of the sintered product, which in turn affects the electrochemical properties and thermal stability of the lithium supplement. The key to the selection of organic solvents lies in their ability to dissolve the sintered product and the stability of the final solution, which directly affects the quality of the lithium supplement precursor.
[0024] By precisely controlling the molar ratio, the optimal interaction between lithium and iron elements can be ensured during sintering or synthesis, thereby improving the capacitance and cycle stability of the final product. Within this molar ratio range, Li5FeO4 with a higher lithium content can be sintered. Particle size control of lithium and iron sources is critical to ensuring material mixing uniformity and reaction efficiency. Smaller particle sizes can increase the surface area of the powder, thereby increasing reaction speed and uniformity. Controlling the particle size within this range can optimize the reaction kinetics of lithium and iron, while reducing particle aggregation problems that may occur during battery manufacturing.
[0025] By precisely controlling the molar ratio and particle size of the lithium source to the iron source, the electrochemical properties of the battery material can be optimized, such as improving the charging capacity and cycle stability. The refined particle size promotes more complete contact between the materials, making the chemical reaction more complete and uniform, thereby improving the quality and performance of the product. The appropriate particle size helps to maintain good fluidity and compactness during the subsequent mixing and compaction process, reducing technical difficulties in production.
[0026] In any of the above technical solutions, sintering includes pre-sintering and formal sintering; the sintering heating rate is 2℃ / min-10℃ / min; and / or the pre-sintering temperature range is 200℃-500℃; and / or the pre-sintering time range is 5h-15h; and / or the formal sintering temperature range is 500℃-900℃; and / or the formal sintering time range is 3h-10h.
[0027] The sintering process includes two stages: pre-sintering and formal sintering, which are carried out under different temperature and time conditions. Staged sintering allows for more detailed and controlled heat treatment of the material. First, pre-sintering eliminates volatile components and pre-shrinkage in the raw materials, and then formal sintering is used to improve the crystal structure and maximize density. The sintering heating rate is set at 2℃ / min-10℃ / min. Controlling the heating rate can prevent cracking or uneven sintering caused by rapid temperature increase, thereby ensuring the structural integrity and performance consistency of the product.
[0028] By sintering in stages and precisely controlling the sintering parameters, the density, uniformity and structural integrity of the material can be significantly improved, thereby optimizing its electrochemical performance and durability. Gradual temperature increase and staged sintering reduce cracks and defects caused by thermal stress or chemical inhomogeneity, enhancing product reliability. By setting clear sintering parameters, the production process is more controllable, which helps to achieve consistency and repeatability in mass production.
[0029] In any of the above technical solutions, the additive is added to the conductive polymer, specifically comprising: adding the additive to the conductive polymer and stirring at a temperature of 50° C.-80° C. for 5 h-8 h.
[0030] One or more additives are directly added to the conductive polymer to improve or enhance specific properties of the polymer. Specifically, the introduction of additives can increase the fluidity of the conductive polymer and make the surface of the lithium ferrite gel-coated. Stirring for 5h-8h at a temperature range of 50℃-80℃ ensures that the additives and the conductive polymer are fully mixed and evenly dispersed. The duration and temperature of stirring are key parameters for optimizing the dispersion effect and chemical reaction.
[0031] In any of the above technical solutions, S30 specifically includes: adding a lithium supplement agent precursor to a conductive polymer, mixing and stirring at a temperature of 45° C.-55° C., and then adding the mixture to a rotary vacuum dryer to obtain a lithium supplement agent.
[0032] The lithium supplement precursor is mixed with the conductive polymer and stirred under controlled specific temperature conditions to ensure uniform mixing, and then a rotary vacuum dryer is used to complete the drying process. By precisely controlling the temperature and using specific drying techniques, the chemical and physical properties of the lithium supplement can be optimized to ensure its efficiency and stability in the final application. The present invention uses a rotary vacuum dryer to dry the carbon in the liquid phase. The rotary vacuum dryer can make the liquid phase coating more uniform during the rotation process. During the drying process, the conductive polymer can be wrapped around the surface of the inner core as it rotates. The conductive polymer can be better attached to the inner core of the lithium supplement due to its own fluidity.
[0033] Specifically, the present invention adopts rotary vacuum drying coating, and the smooth gel-like lithium supplement can be fully mixed with the electrolyte during battery formation, with good infiltration effect. The gel can fill the microcracks in the LFO core and increase the strength of the LFO, so that the anti-fluorite structure in the core of the lithium supplement will not be converted into a disordered rock phase or an amorphous form before the capacity is exerted, and the capacity is exerted more stably and more completely.
[0034] In any of the above technical solutions, the total amount of the conductive polymer and the lithium supplement precursor added is 20%-40% of the capacity of the rotary vacuum dryer; and / or the speed range of the rotary vacuum dryer is 10r / min-20r / min.
[0035] The total amount of conductive polymer and lithium supplement precursor added is controlled at 20%-40% of the capacity of the rotary vacuum dryer. This ratio is optimized based on equipment capacity and processing efficiency to ensure sufficient space for effective stirring and uniform drying. The speed of the rotary vacuum dryer is set between 10r / min-20r / min. This speed range is designed to optimize drying efficiency and prevent uneven drying or damage to the material due to excessive speed.
[0036] By controlling the filling amount of conductive polymer and precursor and the rotation speed of the dryer, it is possible to ensure that the materials are more evenly distributed and dried during the drying process, avoiding aggregation and local overheating, thereby improving the overall quality of the product. The appropriate rotation speed can prevent mechanical damage to the materials caused by excessive rotation speed during the drying process, such as particle breakage, and maintain the integrity and functionality of the product. The appropriate filling amount and rotation speed can achieve the ideal drying effect in a short time, reduce energy consumption and operation time, and improve production efficiency.
[0037] The present invention also provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the lithium supplement agent as described above.
[0038] The positive electrode sheet contains a specially designed lithium supplement, which is prepared by the aforementioned method, and at least part of the surface of the lithium supplement precursor is coated with a conductive polymer. The negative electrode sheet is usually made of carbon material or other suitable negative electrode material. The electrolyte allows lithium ions to move between the positive and negative electrodes, and is usually a liquid or solid electrolyte.
[0039] By using a lithium supplement in the positive electrode, the electric energy stored in the battery per unit volume or weight can be increased, thereby improving the energy density of the battery. Since at least part of the surface of the lithium supplement precursor is coated with a conductive polymer, and the coating is uniform and has good air stability, the gel lithium supplement can be fully mixed with the electrolyte during battery formation, and the infiltration effect is good. The gel can fill the microcracks in the LFO core, increase the strength of the LFO, and prevent the anti-fluorite structure in the lithium supplement core from being converted into a disordered facies or amorphous form before the capacity is exerted, so that the capacity is exerted more stably and completely.
[0040] After adopting the technical solution of the present invention, the following technical effects can be achieved:
[0041] (1) In the prior art, two or three layers of coating are used for carbon coating, and the coating is irregular and amorphous. The present invention uses liquid phase conductive polymer coating, which is more uniform after coating. The gel can fill the microcracks in the LFO core and increase the strength of LFO, so that the anti-fluorite structure of the lithium supplement core will not be converted into disordered rock phase or amorphous form before exerting its capacity;
[0042] (2) The surface of the lithium supplement agent after coating is gel-like. Compared with the irregular carbon coating, the smooth gel-like lithium supplement agent can be fully mixed with the electrolyte during battery formation, with good wetting effect, more stable capacity utilization, and more complete capacity utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0044] Figure 1 A schematic diagram of the structure of a lithium supplement provided by an embodiment of the present invention;
[0045] Figure 2 This is a scanning electron microscope image of the lithium supplement provided in Example 1 of the present invention;
[0046] Figure 3 This is a scanning electron microscope image of the lithium supplement provided in Comparative Example 1 of the present invention;
[0047] Figure 4 This is a scanning electron microscope image of the cracks in the lithium supplement provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0048] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] An embodiment of the present invention provides a lithium supplement agent, which includes a lithium supplement agent precursor and a conductive polymer, wherein the conductive polymer is coated on at least a portion of the surface of the lithium supplement agent precursor; wherein the lithium supplement agent precursor includes Li5FeO4; an additive is added to the conductive polymer, and the additive includes at least one of a water reducer, a dispersant and a surfactant.
[0050] The lithium supplement precursor is used to supplement lithium in lithium-ion batteries, and at least part of the surface of the lithium supplement precursor is coated with a conductive polymer. Conductive polymer coating can improve the capacity of the lithium supplement during the electrochemical cycle, thereby increasing the battery energy density and extending the battery life. Conductive polymers can enhance the overall conductivity of the lithium supplement, allowing lithium ions to migrate more quickly and efficiently within the battery, improving the battery's charge and discharge performance. The coating layer can optimize the interface compatibility between the lithium supplement and the battery electrolyte, reduce potential interface reactions, reduce internal resistance, and further improve battery efficiency.
[0051] The introduction of conductive polymers, especially with the assistance of at least one of additives such as water reducers, dispersants and surfactants, can protect the inner core by forming a gel-like coating layer while compensating for the microcracks on the surface of the inner core of the lithium supplement, so that the anti-fluorite structure of the inner core of the lithium supplement will not be converted into a disordered lithology or amorphous form before its capacity is exerted. In addition, conductive polymers can increase conductivity to solve the problems of poor air stability and poor conductivity of lithium-rich materials during storage.
[0052] like Figure 1 As shown, A is the gel-like filler at the crack, and B is the conductive polymer coating. The conductive polymer can be evenly wrapped on the surface of the lithium supplement core. A water reducer, dispersant or surfactant is added to the conductive polymer to avoid the problem of large particle agglomeration during the coating process, enhance the fluidity of the material, and obtain a denser gel-like film, which can eventually be more evenly attached to the lithium supplement core. The gel-like conductive polymer not only covers the LFO surface, but also fills the microcracks in the LFO core, increases the strength of the LFO, and prevents the lithium supplement core from being converted into a disordered rock phase or amorphous form before the capacity is exerted, ensuring better capacity.
[0053] In some embodiments of the present application, the conductive polymer includes at least one of poly(p-phenylene vinylene), polyaniline, polyphenylene sulfide, polypyrrole, polyacetylene, and polythiophene; and / or the water reducer includes melamine resin; and / or the dispersant includes at least one of polyvinyl pyrrolidone and coconut acid monoethanolamide; and / or the surfactant includes at least one of hexadecyltrimethylammonium bromide, monolauryl phosphate, alcohol ether phosphate, coconut acid diethanolamide, and coconut oil amide propyl dimethylamine ethyl lactone.
[0054] Different types of conductive polymers have their own conductivity, stability and chemical properties. Among them, materials such as polyaniline and polypyrrole have excellent conductivity and good mechanical stability, while polyphenylene sulfide and polythiophene provide good heat resistance and chemical stability. By selecting different conductive polymers, the conductivity, mechanical strength and compatibility of the lithium supplement with the battery electrode can be adjusted.
[0055] As a water reducer, melamine resin can effectively reduce the viscosity of the conductive polymer solution, making it easier to evenly coat the surface of the lithium supplement precursor during the preparation process. At the same time, it can also improve the processability of the lithium supplement during the manufacturing process and prevent excessive adhesion and delamination of the material during the coating process.
[0056] Polyvinyl pyrrolidone and coconut acid monoethanolamide are used as dispersants to effectively prevent the conductive polymer from agglomerating during the preparation process and ensure that the material maintains good dispersion in the solution, which helps to obtain a more uniform coating layer during the coating process while ensuring that the conductive polymer forms a stable network structure on the surface of the precursor.
[0057] Surfactants can significantly improve the interfacial tension between the conductive polymer and the lithium supplement precursor during the coating process, thereby enhancing its adhesion. These surfactants can improve the wettability of the conductive polymer, allowing it to more evenly cover the lithium supplement precursor and form a dense conductive layer. In addition, surfactants can also reduce interfacial defects that may occur during the coating process, such as pinholes and cracks.
[0058] In some embodiments of the present application, the thickness of the coating layer formed by the conductive polymer on the surface of the lithium supplement agent precursor is 5nm-20nm; and / or the particle size D50 of the lithium supplement agent is in the range of 7μm-20μm; and / or the particle size Dmax of the lithium supplement agent is in the range of Dmax≤50μm; and / or the amount of the conductive polymer added is 1wt%-3wt% of the lithium supplement agent.
[0059] By controlling the thickness of the conductive polymer coating within the range of 5nm-20nm, a balance between effective conductivity and economical material use can be achieved. Too thin a thickness will result in insufficient conductivity and the inability to form a continuous conductive path; while too thick a thickness will result in material waste and may increase the internal resistance of the battery, thereby affecting battery performance. In addition, reasonable thickness control can also enhance the adhesion and stability of the conductive layer, reduce delamination or splitting caused by mechanical or electrochemical stress during the cycle, and improve the overall durability and cycle life of the battery.
[0060] The median diameter D50 of the particle size reflects the central trend of the particle size distribution of the lithium supplement. Controlling the particle size D50 of the lithium supplement within the range of 7μm-20μm helps to ensure the uniform distribution of the lithium supplement particles in the battery and optimize its contact area with the electrolyte. Smaller particle sizes are conducive to improving reaction activity and uniformity, while overly large particles will lead to poor contact between particles and affect battery performance. Therefore, the particle size distribution within this range helps to optimize the surface-to-volume ratio of the lithium supplement and improve its electrochemical performance during the battery reaction. At the same time, reasonable particle size control can prevent the sedimentation or accumulation of particles in the battery, ensuring the uniform discharge characteristics and long life of the battery.
[0061] The maximum particle size of the lithium supplement is controlled within 50μm, which can prevent the stratification or agglomeration caused by larger particles during the coating process, thereby affecting the distribution and conductivity of the lithium supplement inside the battery. The control of particle size ensures the uniformity of the material during the coating process and avoids the damage of the conductive network by the presence of large particles. At the same time, this control also helps to optimize the electrode structure and interface quality inside the battery, further improving the performance stability and service life of the battery.
[0062] The amount of conductive polymer added is controlled to be between 1wt% and 3wt% of the total weight of the lithium supplement, while maintaining good conductivity, and avoiding the use of excessive conductive polymer to prevent excessive impact on the properties of the lithium supplement material itself, such as mechanical strength or reactivity. An amount of conductive polymer added below 1wt% may not form a sufficient conductive path, while an amount exceeding 3wt% may increase costs and negatively affect the physical properties of the material.
[0063] An embodiment of the present invention provides a method for preparing a lithium supplement, comprising the following steps: S10, crushing and sintering a lithium source and an iron source in sequence to obtain a lithium supplement precursor; S20, dissolving the lithium supplement precursor in an organic solvent to obtain a mixture; S30, adding the mixture to a conductive polymer, stirring and drying in sequence to obtain a lithium supplement; wherein an additive is added to the conductive polymer, the additive comprising at least one of a water reducer, a dispersant and a surfactant, and the amount of the additive added is 0.2wt%-2wt% of the conductive polymer.
[0064] The invention discloses a preparation method for preparing a lithium supplement agent, wherein the crushing and sintering steps accurately control the particle size and crystal structure of a lithium supplement agent precursor, which is conducive to the efficiency and uniformity of subsequent chemical reactions; the lithium supplement agent precursor is dissolved in an organic solvent to ensure the uniform distribution of chemical components, which is the key to optimizing subsequent reactions and product performance. Specifically, the lithium supplement agent precursor is Li5FeO4 generated by sintering, which is dissolved in an organic solvent to enable LFO to be better combined with a conductive polymer to finally form an LFO core in the product; the introduction of the conductive polymer, especially with the assistance of additives such as a water reducer, a dispersant and a surfactant, not only improves the conductivity of the lithium supplement agent, but also improves its mechanical strength and stability, so that the lithium supplement agent is more suitable for use in batteries, and has better electrochemical properties and a longer service life.
[0065] Through this preparation method, the conductive polymer can be evenly coated on the surface of the lithium supplement core. The additives added to the conductive polymer can avoid the problem of large particle agglomeration during the coating process, enhance the fluidity of the material, and obtain a denser gel-like film, which can eventually be more evenly attached to the lithium supplement core. In addition, the gel-like conductive polymer fills the microcracks in the LFO core, increases the strength of the LFO, and prevents the lithium supplement core from being converted into a disordered rock phase or amorphous form before the capacity is exerted, ensuring better capacity.
[0066] It should be noted that the lithium source and the iron source are poured into the steel mill, and the steel mill is started 5 to 10 times, and each time it lasts for 10 seconds to obtain a crushed mixture, and then prepare for sintering. In step S20, the sintered product is dissolved in an organic solvent and magnetically stirred at room temperature for 5h-10h to obtain a lithium supplement precursor. In step S30, the lithium supplement precursor and the conductive polymer can be mixed and stirred at 45°C-55°C, and then added to a rotary vacuum dryer for drying to obtain Li5FeO4 coated with a conductive polymer; the lithium supplement precursor can also be added to a rotary vacuum dryer first, and vacuum heated to 45°C-55°C, filled with nitrogen to balance the vacuum pressure, and then a conductive polymer doped with an additive is added, and vacuum drying is continued to obtain Li5FeO4 coated with a conductive polymer.
[0067] In the process of preparing the conductive polymer, ensure that the amount of additive added is accurately controlled between 0.2wt% and 2wt% of the total weight of the polymer. This ratio range is intended to ensure that the additive can work effectively while avoiding unnecessary cost increases or possible negative effects caused by excessive use. By controlling the amount of additive, while enhancing the performance of the polymer, controlling costs and avoiding the additional burden caused by excessive addition; mechanical strength or other related properties, without interfering with the basic structure of the material. Preferably, the amount of additive added is 0.8wt%-1.5wt% of the conductive polymer.
[0068] In some embodiments of the present application, the lithium source includes at least one of LiOH, Li2CO3, Li2O, Li2O2, LiNO3, Li2SO4, C6H5Li3O7, Li2C2O4, C2H5OLi, and metallic lithium; and / or the iron source includes at least one of Fe2O3, Fe3O4, Fe(OH)3, and FeO(OH); and / or the organic solvent is at least one of tetrahydrofuran, N-methylpyrrolidone, and dimethyl sulfoxide; and / or the molar ratio of the lithium source to the iron source is (5-7): 1; and / or after the lithium source and the iron source are crushed, their particle size D50 is 5μm-70μm.
[0069] Lithium sources have different chemical properties and reactivity, and these lithium sources provide multiple possibilities for the preparation process, thereby adjusting the performance and efficiency of the lithium supplement. The choice of iron source affects the magnetism and structural stability of the sintered product, and then affects the electrochemical properties and thermal stability of the lithium supplement. The key to the selection of organic solvents lies in their solubility in the sintered product and the stability of the final solution, which directly affects the quality of the lithium supplement precursor. Among them, the selected lithium source and iron source can react to produce Li5FeO4, i.e. LFO, required in this embodiment. The organic solvent is at least one of tetrahydrofuran (THF), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO). It should be noted that the organic solvent does not need to control the proportion, it only needs to combine LFO and the conductive polymer together, and the role of the organic solvent is to better ensure the combination and contact of LFO and the conductive polymer.
[0070] By precisely controlling the molar ratio of lithium source to iron source, the optimal interaction between lithium and iron elements can be ensured during sintering or synthesis, thereby improving the capacitance and cycle stability of the final product. Within this molar ratio range, Li5FeO4 with a higher lithium content can be sintered. Particle size control of lithium and iron sources is critical to ensuring material mixing uniformity and reaction efficiency. Smaller particle size can increase the surface area of the powder, thereby increasing reaction speed and uniformity. Controlling particle size within this range can optimize the reaction kinetics of lithium and iron, while reducing particle aggregation problems that may occur during battery manufacturing.
[0071] By precisely controlling the molar ratio and particle size of the lithium source to the iron source, the electrochemical properties of the battery material can be optimized, such as improving the charging capacity and cycle stability. The refined particle size promotes more complete contact between the materials, making the chemical reaction more complete and uniform, thereby improving the quality and performance of the product. The appropriate particle size helps to maintain good fluidity and compactness during the subsequent mixing and compaction process, reducing technical difficulties in production. Preferably, the molar ratio of the lithium source to the iron source is (4-6): 1; and / or after the lithium source and the iron source are crushed, the particle size D50 is 5μm-40μm.
[0072] In some embodiments of the present application, sintering includes pre-sintering and formal sintering; the sintering heating rate is 2°C / min-10°C / min; and / or the pre-sintering temperature range is 200°C-500°C; and / or the pre-sintering time range is 5h-15h; and / or the formal sintering temperature range is 500°C-900°C; and / or the formal sintering time range is 3h-10h.
[0073] The sintering process includes two stages: pre-sintering and formal sintering, which are carried out under different temperature and time conditions. Staged sintering allows for more detailed and controlled heat treatment of the material. First, pre-sintering eliminates volatile components and pre-shrinkage in the raw materials, and then formal sintering is used to improve the crystal structure and maximize density. The sintering heating rate is set at 2℃ / min-10℃ / min. Controlling the heating rate can prevent cracking or uneven sintering caused by rapid temperature increase, thereby ensuring the structural integrity and performance consistency of the product.
[0074] By sintering in stages and precisely controlling the sintering parameters, the density, uniformity and structural integrity of the material can be significantly improved, thereby optimizing its electrochemical performance and durability. Gradual heating and staged sintering reduce cracks and defects caused by thermal stress or chemical inhomogeneity, and enhance the reliability of the product. By setting clear sintering parameters, the production process is more controllable, which helps to achieve consistency and repeatability in mass production. Preferably, the sintering heating rate is 4℃ / min-7℃ / min, the pre-sintering temperature range is 250℃-400℃, the pre-sintering time range is 7h-12h, the formal sintering temperature range is 600℃-800℃, and the formal sintering time range is 4h-7h.
[0075] In some embodiments of the present application, an additive is added to the conductive polymer, specifically comprising: adding the additive to the conductive polymer and stirring at a temperature of 50° C.-80° C. for 5 h-8 h.
[0076] One or more additives are directly added to the conductive polymer to improve or enhance specific properties of the polymer. Specifically, the introduction of additives can increase the fluidity of the conductive polymer and make the surface of the lithium ferrite gel-coated. Stirring for 5h-8h at a temperature range of 50℃-80℃ ensures that the additives and the conductive polymer are fully mixed and evenly dispersed. The duration and temperature of stirring are key parameters for optimizing the dispersion effect and chemical reaction.
[0077] In some embodiments of the present application, S30 specifically includes: adding a lithium supplement agent precursor to a conductive polymer, mixing and stirring at a temperature of 45° C. to 55° C., and then adding the mixture to a rotary vacuum dryer to obtain a lithium supplement agent.
[0078] The lithium supplement precursor is mixed with the conductive polymer and stirred under controlled specific temperature conditions to ensure uniform mixing, and then a rotary vacuum dryer is used to complete the drying process. By precisely controlling the temperature and using specific drying techniques, the chemical and physical properties of the lithium supplement can be optimized to ensure its efficiency and stability in the final application. The present invention uses a rotary vacuum dryer to dry the carbon in the liquid phase. The rotary vacuum dryer can make the liquid phase coating more uniform during the rotation process. During the drying process, the conductive polymer can be wrapped around the surface of the inner core as it rotates. The conductive polymer can be better attached to the inner core of the lithium supplement due to its own fluidity.
[0079] Specifically, the present invention adopts rotary vacuum drying coating, and the smooth gel-like lithium supplement can be fully mixed with the electrolyte during battery formation, with good infiltration effect. The gel can fill the microcracks in the LFO core and increase the strength of the LFO, so that the anti-fluorite structure in the core of the lithium supplement will not be converted into a disordered rock phase or an amorphous form before the capacity is exerted, and the capacity is exerted more stably and more completely.
[0080] Furthermore, stirring within a specified temperature range can promote an effective reaction between the conductive polymer and the precursor, thereby improving the quality and performance of the final product. The rotary vacuum dryer can more effectively control the moisture content of the product, reduce the difference between batches, and ensure the stability of each batch of products. The rotary vacuum dryer is used for drying at a lower temperature, reducing energy consumption while speeding up the production cycle and improving overall production efficiency.
[0081] In some embodiments of the present application, the total amount of the conductive polymer and the lithium supplement precursor added is 20%-40% of the capacity of the rotary vacuum dryer; and / or the rotation speed of the rotary vacuum dryer ranges from 10r / min to 20r / min.
[0082] The total amount of conductive polymer and lithium supplement precursor added is controlled at 20%-40% of the capacity of the rotary vacuum dryer. This ratio is optimized based on equipment capacity and processing efficiency to ensure sufficient space for effective stirring and uniform drying. The speed of the rotary vacuum dryer is set between 10r / min-20r / min. This speed range is intended to optimize drying efficiency and prevent uneven drying or damage to the material due to excessive speed. Preferably, the total amount of conductive polymer and lithium supplement precursor added is 25%-35% of the capacity of the rotary vacuum dryer, and the speed range of the rotary vacuum dryer is 13r / min-17r / min.
[0083] By controlling the filling amount of conductive polymer and precursor and the rotation speed of the dryer, it is possible to ensure that the materials are more evenly distributed and dried during the drying process, avoiding aggregation and local overheating, thereby improving the overall quality of the product. The appropriate rotation speed can prevent mechanical damage to the materials caused by excessive rotation speed during the drying process, such as particle breakage, and maintain the integrity and functionality of the product. The appropriate filling amount and rotation speed can achieve the ideal drying effect in a short time, reduce energy consumption and operation time, and improve production efficiency.
[0084] An embodiment of the present invention further provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the lithium supplement as described above.
[0085] The positive electrode sheet contains a specially designed lithium supplement, which is prepared by the aforementioned method, and at least part of the surface of the lithium supplement precursor is coated with a conductive polymer. The negative electrode sheet is usually made of carbon material or other suitable negative electrode material. The electrolyte allows lithium ions to move between the positive and negative electrodes, and is usually a liquid or solid electrolyte.
[0086] By using a lithium supplement in the positive electrode, the electric energy stored in the battery per unit volume or weight can be increased, thereby improving the energy density of the battery. Since at least part of the surface of the lithium supplement precursor is coated with a conductive polymer, and the coating is uniform and has good air stability, the gel lithium supplement can be fully mixed with the electrolyte during battery formation, and the infiltration effect is good. The gel can fill the microcracks in the LFO core, increase the strength of the LFO, and prevent the anti-fluorite structure in the lithium supplement core from being converted into a disordered facies or amorphous form before the capacity is exerted, so that the capacity is exerted more stably and completely.
[0087] Example 1
[0088] An embodiment of the present invention provides a method for preparing a lithium supplement, comprising the following steps:
[0089] S1. LiOH and Fe2O3 are weighed separately according to the molar ratio of lithium element to iron element of 5:1;
[0090] S2, putting LiOH and Fe2O3 into a steel mill and grinding and mixing, the steel mill is started 5 times and each time lasts for 10 seconds to obtain a mixture; the particle size D50 of the lithium source and the iron source after crushing is 20 μm;
[0091] S3, putting the mixture into a sagger and sintering it in a tube furnace, with a heating rate of 2°C / min, heating to 500°C in the first stage, keeping it warm for 15 hours, heating to 900°C in the second stage, keeping it warm for 10 hours, and cooling it in the furnace to obtain sintered Li5FeO4;
[0092] S4, dissolving Li5FeO4 in THF, and magnetically stirring at room temperature for 5 h to obtain a mixture A;
[0093] S5, adding polyvinyl pyrrolidone to poly(p-styrene), stirring at 50° C. for 5 h, to obtain a mixture B; the amount of polyvinyl pyrrolidone added is 0.2 wt % of the poly(p-styrene);
[0094] S6. Add mixture A and mixture B into a rotary vacuum dryer, heat to about 50°C under vacuum, fill with nitrogen to balance the vacuum pressure, and continue vacuum drying. The total amount of mixture A and mixture B added is 20% of the drying barrel. The rotation speed of the drying barrel is 10r / min. After drying, the coated Li5FeO4 is obtained.
[0095] Figure 2 This is a scanning electron microscope image of the lithium supplement prepared in Example 1.
[0096] The thickness of the conductive polymer coating is tested as follows: SEM uses an electron beam to scan the surface of the sample and detects the secondary electron signal generated, thereby generating a high-resolution surface image. After the sample is metallized, its cross section is scanned by SEM to measure the thickness of the coating. The thickness of the conductive polymer coating in Example 1 is finally measured to be 8nm. The particle size D50 of the lithium supplement in Example 1 is 7μm; the particle size Dmax of the lithium supplement is 38μm. The amount of conductive polymer added is 1.5wt% of the lithium supplement.
[0097] Example 2
[0098] An embodiment of the present invention provides a method for preparing a lithium supplement, comprising the following steps:
[0099] S1. LiOH and Fe3O4 are weighed separately according to the molar ratio of lithium element to iron element of 7:1;
[0100] S2, putting LiOH and Fe3O4 into a steel mill and grinding and mixing, the steel mill is started 10 times and each time lasts for 10 seconds to obtain a mixture; the particle size D50 of the lithium source and the iron source after crushing is 35 μm;
[0101] S3, putting the mixture into a sagger and sintering it in a tube furnace, with a heating rate of 10°C / min, heating to 300°C in the first stage, keeping it warm for 8 hours, heating to 600°C in the second stage, keeping it warm for 5 hours, and cooling it in the furnace to obtain sintered Li5FeO4;
[0102] S4, dissolving Li5FeO4 in NMP, and magnetically stirring at room temperature for 5 h to obtain mixture A;
[0103] S5, adding hexadecyltrimethylammonium bromide to polyaniline, stirring at 60° C. for 6 hours, to obtain a mixture B; the amount of hexadecyltrimethylammonium bromide added is 0.5wt% of the polyaniline;
[0104] S6. Add mixture A and mixture B into a rotary vacuum dryer, heat to about 50°C under vacuum, fill with nitrogen to balance the vacuum pressure, and continue vacuum drying. The total amount of mixture A and mixture B added is 25% of the drying barrel. The rotation speed of the drying barrel is 13r / min. After drying, the coated Li5FeO4 is obtained.
[0105] The thickness of the conductive polymer coating layer in Example 2 was measured to be 13 nm. The particle size D50 of the lithium supplement agent in Example 2 was 15 μm; the particle size Dmax of the lithium supplement agent was 42 μm. The amount of conductive polymer added was 1.8 wt% of the lithium supplement agent.
[0106] Example 3
[0107] The embodiment of the present invention provides a method for preparing a lithium supplement. The specific steps are shown in Example 1. The difference from Example 1 is that in S1, Li2O is used instead of LiOH, and Fe(OH)3 is used instead of Fe2O3; in S4, DMSO is used instead of THF; in S5, monolauryl phosphate is used instead of polyvinyl pyrrolidone, and polythiophene is used instead of poly(p-phenylene glycol).
[0108] Example 4
[0109] The embodiment of the present invention provides a method for preparing a lithium supplement. The specific steps are shown in Example 1. The difference from Example 1 is that in S1, Li2CO3 is used instead of LiOH; FeO(OH) is used instead of Fe2O3; in S4, DMSO is used instead of THF; in S5, melamine resin is used instead of polyvinyl pyrrolidone; and polyphenylene sulfide is used instead of poly(p-phenylene)ene.
[0110] Example 5
[0111] The embodiment of the present invention provides a method for preparing a lithium supplement. The specific steps are shown in Example 1. The difference from Example 1 is that in S1, C2H5OLi is used instead of LiOH; in S4, NMP is used instead of THF; in S5, melamine resin and coconut oil monoethanolamide are used instead of polyvinyl pyrrolidone; polyacetylene is used instead of poly(p-styrene).
[0112] Example 6
[0113] The embodiment of the present invention provides a method for preparing a lithium supplement. The specific steps are as shown in Example 1. The difference from Example 1 is that in S5, melamine resin, polyvinyl pyrrolidone and alcohol ether phosphate are used instead of polyvinyl pyrrolidone.
[0114] Comparative Example 1
[0115] The comparative example of the present invention provides a method for preparing a lithium supplement agent. The specific steps are shown in Example 1. The difference from Example 1 is that after sintering into Li5FeO4, a common solid phase coating method is directly used for preparation, that is, the carbon source and Li5FeO4 are placed in a steel mill for mixing, and the solid-phase coated Li5FeO4 is obtained after mixed sintering.
[0116] Figure 3 This is a scanning electron microscope image of the lithium supplement prepared in Comparative Example 1; Figure 4 This is a scanning electron microscope image of the cracks in the lithium supplement in Comparative Example 1.
[0117] Comparative Example 2
[0118] The comparative example of the present invention provides a method for preparing a lithium supplement. The specific steps are as shown in Example 1. The difference from Example 1 is that no water reducing agent, dispersant or surfactant is added during the liquid phase experiment.
[0119] Comparative Example 3
[0120] The comparative example of the present invention provides a method for preparing a lithium supplement. The specific steps are shown in Example 1. The difference from Example 1 is that during the liquid phase experiment, the amount of water reducing agent, dispersant or surfactant added is 3wt% of the conductive polymer.
[0121] Performance Test:
[0122] The products of the above-mentioned Examples 1-4 and Comparative Examples 1-3 were added to soft-pack batteries for electrochemical performance testing and standing time, wherein the positive electrode was commercial NCM811, the negative electrode was commercial silicon-carbon negative electrode composite graphite, the electrolyte included 1 mol / L LiPF6, EC and EMC with a mass ratio of 7:3, and 1% FEC, the battery capacity was 5.0Ah, the formation cut-off voltage was 4.3V, the cycle voltage range was 2.8V-4.2V, the charge and discharge rate was 0.1C, and the first charge capacity and the capacity retention rate after 100 cycles were tested. The test results are shown in Table 1.
[0123] Table 1 Test results of Examples 1-4 and Comparative Examples 1-3
[0124]
[0125] Result analysis:
[0126] The test results of Example 1 and Comparative Example 1 show that Figure 1 It can be seen that the capacity change of the lithium supplement in Example 1 after exposure for 24 hours is 20.35 mAh / g. Since a gel-like protective layer is formed on the surface of the core, water vapor in the air cannot corrode the core, and the capacity retention rate is 97.18%. Figure 2 It can be seen that the lithium supplement agent in comparative example 1 has uneven coating, which makes the capacity not fully utilized. After exposure for 24 hours, its capacity decreases by 195.32 mAh / g. This is because under the exposure environment, water vapor in the air invades the core of the lithium supplement agent, and the core partially deteriorates, resulting in a decrease in capacity. The capacity retention rate is only 69.84%. Figure 3 It can be seen that the cracks existing in the lithium supplement agent of Comparative Example 1 are not filled by the coating layer.
[0127] The test results of Example 1 and Comparative Example 2 show that no water reducing agent, dispersant or surfactant was added during the liquid phase experiment, resulting in a poor coating effect. The initial charging capacity of Comparative Example 2 was 70.11 mAh / g lower than that of Example 1, and the capacity retention rate was 95.37% after exposure for 24 hours. Compared with Example 1, the capacity retention rate of Comparative Example 2 decreased.
[0128] The test results of Example 1 and Comparative Example 3 show that adding excessive water reducer, dispersant or surfactant will affect the capacity of the lithium supplement agent, and its capacity is only 628.89 mAh / g. The first charging capacity of Comparative Example 3 is 94.63 mAh / g lower than that of Example 1, and the capacity retention rate after 24 hours is 95.13%. Compared with Example 1, the capacity retention rate of Comparative Example 3 is reduced.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium supplement, characterized in that: The lithium supplement agent comprises a lithium supplement agent precursor and a conductive polymer, wherein the conductive polymer liquid phase is coated on at least a portion of the surface of the lithium supplement agent precursor; Wherein, the lithium supplement precursor includes Li5FeO4; the conductive polymer is added with an additive, and the additive includes at least one of a water reducing agent, a dispersant and a surfactant; The water reducing agent includes melamine resin; The dispersant includes at least one of polyvinyl pyrrolidone and coconut oil monoethanolamide; The surfactant includes at least one of cetyl trimethyl ammonium bromide, monolauryl phosphate, alcohol ether phosphate, coconut oil diethanolamide, and cocamidopropyl dimethylamine ethyl lactone.
2. The lithium supplement according to claim 1, characterized in that: The conductive polymer includes at least one of poly(p-phenylene vinylene), polyaniline, polyphenylene sulfide, polypyrrole, polyacetylene and polythiophene.
3. The lithium supplement according to claim 1, characterized in that: The thickness of the coating layer formed by the conductive polymer on the surface of the lithium supplement agent precursor is 5nm-20nm; and / or The particle size D50 of the lithium supplement agent is in the range of 7 μm-20 μm; and / or The particle size Dmax of the lithium supplement agent is in the range of Dmax≤50 μm; and / or The added amount of the conductive polymer is 1wt%-3wt% of the lithium supplement agent.
4. A method for preparing a lithium supplement, characterized in that: The preparation method is used to prepare the lithium supplement according to any one of claims 1 to 3, and the preparation method comprises the following steps: S10, crushing and sintering the lithium source and the iron source in sequence to obtain the lithium supplement agent precursor; S20, dissolving the lithium supplement agent precursor in an organic solvent to obtain a mixture; S30, adding the mixture to the conductive polymer, stirring and drying in sequence to obtain the lithium supplement agent; The conductive polymer is added with the additive, which includes at least one of a water reducing agent, a dispersant and a surfactant, and the additive is added in an amount of 0.2wt%-2wt% of the conductive polymer.
5. The preparation method according to claim 4, characterized in that: The lithium source comprises at least one of LiOH, Li2CO3, Li2O, Li2O2, LiNO3, Li2SO4, C6H5Li3O7, Li2C2O4, C2H5OLi, and metallic lithium; and / or The iron source comprises at least one of Fe2O3, Fe3O4, Fe(OH)3 and FeO(OH); and / or The organic solvent is at least one of tetrahydrofuran, N-methylpyrrolidone and dimethyl sulfoxide; and / or The molar ratio of the lithium source to the iron source is (5-7):1; and / or After the lithium source and the iron source are pulverized, the particle size D50 thereof is 5 μm-70 μm.
6. The preparation method according to claim 4, characterized in that: The sintering includes pre-sintering and formal sintering; The heating rate of the sintering is 2°C / min-10°C / min; and / or The pre-sintering temperature ranges from 200°C to 500°C; and / or The pre-sintering time ranges from 5h to 15h; and / or The temperature range of the formal sintering is 500°C-900°C; and / or The time range of the formal sintering is 3h-10h.
7. The preparation method according to claim 4, characterized in that: The conductive polymer is added with the additive, which specifically includes: The additive is added into the conductive polymer and stirred at a temperature of 50° C. to 80° C. for 5 h to 8 h.
8. The preparation method according to claim 4, characterized in that: S30 specifically includes: The lithium supplement agent precursor is added to the conductive polymer, mixed and stirred at a temperature of 45° C. to 55° C., and then added to a rotary vacuum dryer to obtain the lithium supplement agent.
9. The preparation method according to claim 8, characterized in that: The total amount of the conductive polymer and the lithium supplement precursor added is 20%-40% of the capacity of the rotary vacuum dryer; and / or The rotation speed range of the rotary vacuum dryer is 10r / min-20r / min.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the lithium supplement agent according to any one of claims 1 to 3.
Citation Information
Patent Citations
Polyaniline coated ternary positive electrode material, preparation method, battery positive electrode and lithium battery thereof
CN108172759A
Organic matter coated multi-element positive electrode material, preparation method and application thereof, and lithium ion battery
CN114695852A